(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This article is aligned with previous studies that evaluate the impact of J. B. Watson’s work in the early twentieth century, but seeks to surpass certain methodological hindrances that could limit the interpretation of its data, such as the absence of comparative parameters. To this end, citations of Watson are compared with citations of eight other relevant psychologists in eight journals in the decade between 1924 and 1933. The results from this bibliometric analysis are compared with data from previous studies, in order to complement, to corroborate or to contest their conclusions. In the examined period, there’s still an increasing tendency towards the expansion of the impact of Watson’s work already observed over the decade immediately after the publication of the Behaviorist Manifesto (1913). Watson’s impact remains close to Dewey’s and Titchener’s, already exceeds Thorndike’s, remains greater compared to Angell, Carr, Cattell and Hall, but yet far from James’s.